2008
DOI: 10.1002/ijc.23911
|View full text |Cite
|
Sign up to set email alerts
|

A Joinpoint regression analysis of long‐term trends in cancer mortality in Japan (1958–2004)

Abstract: Cancer is one of the major targets of disease control programs in Japan. A Joinpoint regression model was used to analyze the longterm trends of mortality related to overall cancer and the 15 most common cancers based on published data from the National Vital Statistics of Japan between 1958 and 2004. Since 1996, a decline has been seen in overall cancer for both sexes in Japan. Most of the common sites, including cancers of the stomach, colon, liver, gallbladder and lung and leukemia in both sexes, cancer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 32 publications
0
85
0
3
Order By: Relevance
“…In Japan, a joinpoint regression model was used to analyze the long-term trends in mortality from 1958 to 2004 (23) and found a favorable trend in risk of colon cancer for both men (APC: -1.23; P<0.05) and women (APC: -0.52; P<0.05) in the early '90s. They also observed a favorable trend in the risk of rectum cancer in men over the same period as our study; however, in women, this trend was observed in the early 1970s, which differed from our results.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, a joinpoint regression model was used to analyze the long-term trends in mortality from 1958 to 2004 (23) and found a favorable trend in risk of colon cancer for both men (APC: -1.23; P<0.05) and women (APC: -0.52; P<0.05) in the early '90s. They also observed a favorable trend in the risk of rectum cancer in men over the same period as our study; however, in women, this trend was observed in the early 1970s, which differed from our results.…”
Section: Discussionmentioning
confidence: 99%
“…Age-standardized mortality rates of ovarian cancer in Japan increased four-fold, from 0.9 to 3.6 per 100,000 women, between the 1950s and the 1990s (4). In the past two decades they have stabilized, reaching 3.3 per 100,000 women in 2004 (5), which is slightly below the worldwide estimates for that year (3.8 per 100,000) (3). Studies on migrants suggest that ovarian cancer incidence rates are higher among Japanese women born in the United States than among those born in Japan (6).…”
Section: Introductionmentioning
confidence: 87%
“…Pancreatic ductal adenocarcinoma is one of the leading causes of death in Japan, and the incidence of this cancer is increasing (1,2). Adenocarcinoma involving the whole pancreas constitutes approximately 1% of all pancreatic cancers in Japan (3).…”
Section: Introductionmentioning
confidence: 99%